EARNING MANAGEMENT IN BANKING SECTOR ON INDONESIA STOCK EXCHANGE: Manajemen Laba di Sektor Perbankan di Bursa Efek Indonesia - Esty Apridasari (International Journal of Economics and Management Research, 2022)
The practice of earnings management could not be separated from the process of preparing financial statements. It could occur in all business sectors including banking. This study aims to analyze earnings management in financial statements of banks on Indonesian Stock Exchange. This research is a descriptive study of banks listed on Indonesia Stock Exchange in 2020. Earnings management in bank financial statements is proxied by discretionary accruals. The population and sample of this research are 42 banks. The results show that 31 banks have a negative Discretionary Accruals and 11 banks have a positive Discretionary Accruals. A negative discretionary accruals indicates that the company performs earnings management by decreasing earnings while a positive discretionary accruals indicates that the company performs earnings management by increasing the earnings in the financial statements.